2009
DOI: 10.1093/ejechocard/jen304
|View full text |Cite
|
Sign up to set email alerts
|

Proximal aortic stiffness is related to left ventricular function and exercise capacity in patients with dilated cardiomyopathy

Abstract: Patients with NIDC showed increased proximal aortic stiffness, which relates to LV systolic and diastolic function and exercise capacity. The echocardiographic assessment of the regional aorta PWV seems to be clinically important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…The results are similar to a recent study of non-ischaemic cardiomyopathy, which demonstrated that there is a significant association between exercise capacity and aortic stiffness, measured by ultrasound 31. However, unlike that study, there was no significant association between pVO 2 and LV diastolic variables, probably owing to substantially different patient populations.…”
Section: Discussionsupporting
confidence: 85%
“…The results are similar to a recent study of non-ischaemic cardiomyopathy, which demonstrated that there is a significant association between exercise capacity and aortic stiffness, measured by ultrasound 31. However, unlike that study, there was no significant association between pVO 2 and LV diastolic variables, probably owing to substantially different patient populations.…”
Section: Discussionsupporting
confidence: 85%
“…24 Similarly, our group found a correlation between echocardiographic aortic elastic properties and peak VO 2 , given their role as independent predictor of exercise capacity in HF patients with DCM. 24 Similarly, our group found a correlation between echocardiographic aortic elastic properties and peak VO 2 , given their role as independent predictor of exercise capacity in HF patients with DCM.…”
Section: Discussionsupporting
confidence: 55%
“…However, several reports have demonstrated that alterations in ventriculo-vascular coupling may be a cofactor in the pathogenesis of heart failure. Increased arterial wave reflection and stiffness have been described in patients with systolic heart failure [17,18,47,48], and brain natriuretic peptide, a marker of severity of heart failure with prognostic value, has been shown to be strongly associated with increased aortic stiffness in the setting of idiopathic dilated cardiomyopathy and in patients with CAD [49,50]. Alterations in arterial stiffness and wave reflection have also been documented in patients with heart failure and normal ejection fraction [10,19,46].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the progressive stiffening of the elastic arteries, cardiac afterload increases both directly (because of a reduction in the Windkessel function) and indirectly (because the accelerated return from periphery of the arterial wave reflection that adds to the resistance to the LV ejection effort) [68]. Indicators of increased arterial wave reflection are independent predictors of coronary artery disease, heart failure, cardiovascular events, and mortality [916], and alterations in ventriculo-vascular coupling have been advocated as possible factors involved in the pathogenesis of both systolic [17,18] and diastolic heart failure [19,20]. …”
Section: Introductionmentioning
confidence: 99%